Immunity in plants and animals: common ends through different means using similar tools - Menezes, H.; Jared, C. (Elsevier B.V., 2002)
A comparative approach is potentially useful for understanding the role of mammal innate immunity role in stimulating adaptive immunity as well as the relationship between these two types of immune strategies. Considerable progress has been made in the elucidation of the co-ordinated events involved in plant perception of infection and their mobilisation of defence responses. Although lacking immunoglobulin molecules, circulating cells, and phagocytic processes, plants successfully use pre-formed physical and chemical innate defences, as well as inducible adaptive immune strategies. In the present paper, we review some shared and divergent immune aspects present in both animals and plants. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: immunity; comparative immunity; plant immunity; innate and adaptive immunity; plant defence; systemic acquired resistance; hypersensitive response; host-parasite interaction; plant immunisation